Penerapan Nesting terhadap Kualitas Tidur Bayi Berat Lahir Rendah (BBLR) di RSUD Ir. Soekarno Sukoharjo - Dewi Setyaningsih; Maryatun Maryatun; Yohana Ika Prastiwi (Jurnal Anestesi, 2024)
Babies born with LBW conditions are more susceptible to disease and have a smaller chance of survival. Low birth weight (LBW) babies can cause developmental disorders both cognitively and motorically. Sleep is an important stage in repairing the neurological system in newborn babies. Poor quality sleep can cause illness and also cause psychological problems in LBW babies. Various developmental care efforts are made to minimize the negative impacts that arise during the treatment period, namely by optimizing the sleep quality of LBW babies, one way is by implementing nesting. Find out the results of the implementation of Nesting on the Sleep Quality of Low Birth Weight (LBW) Babies at the Ir. Soekarno Sukoharjo Regional Hospital. This type of research is a case study that uses descriptive pretest posttest design research methods and uses measurements of baby sleep quality. The results of the application to 2 respondents which were carried out for 2 days showed that there was an effect of nesting on improving the sleep quality of LBW babies. There were differences in the results before and after the nesting intervention on the sleep quality of LBW babies.